(untitled) (Mongolian Journal of Arts and Culture, 2024)
When the ikhel has developed and spread out for a long historic period it has preserved its performing technique. But at present the tradition of this performing technique of the ikhel has been lost and the peculiarities of the ethnic group of each region have to be mixed with each other and have been destroyed and decreased. So we considered the technique of the ikhel, performed by Jutaan Khumbaa,ikhel-player andbii dancer of Malchin soum, Uvs province, who is the best tradition bearer of the year of 2020 of the intangible cultural heritage. Баядын ихэлч Жутаан Хумбаагийн ихэл татах арга барилын онцлог Хураангуй: Ихэл нь түүхэн цаг хугацаанд хөгжин дэлгэрч ирэхдээ хөгжимдөх арга барилаа хадгалсаар ирсэн хэдий ч өнөө үед ихэлийн татлагын язгуур байдал нь алдагдаж, бүс нутаг бүрийн угсаатны бүлгийн өвөрмөц шинжүүд өөр хоорондоо холилдоход хүрч, устаж цөөрсөөр байна. Иймээс ихэлийн татлагыг гарамгай эзэмшсэн соёлын биет бус өвийн 2020 оны шилдэг өвлөн уламжлагч Увс аймгийн Малчин сумын ихэлч, бийч Жутаан Хумбаагийн ихэл татах арга барилын талаар авч үзэх болно. Түлхүүр үгс: ихэл, ихэлийн татлага, ихэлч Хумбаа, ноот